Analisa Pengukuran Parameter Quality of Service dan Quality of Experience pada Layanan HbbTV - Putri, RA Rizka Qori Yuliani; Ery Safrianti; Salpiana; Jesica Amanda Putri; Sucahyo Grianto; Aji Noor Hakim (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2023)
Hybrid Broadcast Broadband TV (HbbTV) is delivery standard for signaling, transmission, presentation of enhanced interactive television services and related applications, designed for use over broadcast networks and Internet. It is only standard that allows direct connection between linear and online content. It works on hybrid devices that include both broadcast and Internet connections. This standard will bring new dimension to services delivered through television programs (TV and Internet) and enhance consumer user experience by enabling innovative and interactive services over broadcast and broadband networks. improve. The HbbTV specification was developed by the HbbTV Association to effectively manage the rapidly increasing amount of content for today's consumers. HbbTV is a technology that combines traditional television broadcasts with Internet services and interactive applications. This research focuses on role of QoS and QoE in HbbTV implementations and measurement of parameters using Wireshark software that affect quality of service and user experience. The research method is experiment measuring QoS and QoE parameters. The QoS measurements were average throughput 47531,8bps, packet loss 4,9968%, delay 189.38ms, jitter 17700ms. We also conducted QoE measurement survey to collect user data to be collected. Data analysis revealed that 7.7% of consumer expectations of HbbTV users need to be improved.